FLEKSIBILITAS PEMBELAJARAN MELALUI PENGAJARAN VIRTUAL BERBASIS WEB DAN SISTEM LABORATORIUM VIRTUAL - Nofri Hendri; Septriyan Anugrah; Diah Anggraini Austin (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2022)
Most educational institutions currently use a web-based virtual teaching system using platforms such as e-learning and carry out learning activities using a virtual laboratory system for practicum of several subjects or courses. Web-based teaching is a possible and economical solution to this problem. The web-based program will automatically correct students' answers to quizzes, and lecturers can obtain and monitor student feedback in real time without delay. The aim of the current design is to provide a more engaging and interactive environment for students to learn. To find out how this virtual systems approach might affect student learning and to get their views on this new teaching approach, the lecturer randomly selected 8 students from this group of 80 students and interviewed them using open-ended questions. According to the results of the questionnaire, most of the students showed positive attitudes towards the virtual system and found that the system encouraged and motivated them to learn better. Most students are interested in learning through virtual teaching (VT; 89%) and experimenting through virtual laboratories (VL; 88%). In accordance with this explanation, learning through web-based virtual teaching and virtual laboratory systems is very flexible to use.Keywords : Flexibility, Virtual Teaching, Web-Based, Virtual Laboratory System.